Impact of Fossil Fuels on Climate and Economy in Indonesia - Erwinsyah, Erwinsyah (International Journal of Energy Economics and Policy, 2025)
The use of fossil fuels and economic growth must be balanced with environmental concerns, and Indonesia is affected by these issues. To examine the relationship between its Gross Domestic Product (GDP), population, energy consumption, and Carbon Dioxide (CO2) emissions in Indonesia, using an econometric model, and utilizing data from the World Bank and Our World in Data, spanning 1995 to 2022. Several tests are used to assess stationarity, cointegration, short- and long-term dynamics, and the response of CO2 emissions to shocks from other variables. Increased energy consumption results in a significant increase in CO2 emissions, whereas economic growth (GDP) has a substantial negative effect, indicating decoupling. The long-term impact of the population shows a negative correlation, but it is not statistically significant. Energy consumption emerged as the most influential variable impacting long-term CO2 emissions, followed by GDP. Considering the long-term influence of energy and the short-term impact of population, Indonesia’s policies should prioritize two areas: (1) reducing emissions from energy consumption, rapidly shifting the energy system towards renewable sources, and implementing robust energy efficiency strategies; and (2) managing population growth and implementing sustainable development strategies to mitigate indirect impacts on resources and CO2 emissions.